The Role of SAKIP-Based Management Information Systems in the Transparency of Local Government Performance Reporting in Indonesia - Rudy Usman; Andi Indriani Ibrahim; Shela Ramadhani; Guan Kusuma; Taufik Afdal; Nini Andriani (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Based on the results of the analysis, this study found that the level of transparency in local government performance reporting in Indonesia is generally high and relatively uniform across regions, although the Government Agency Performance Accountability System (SAKIP) scores show significant variation and the average is still low. However, the relationship between the implementation of SAKIP and the level of transparency proved to be very weak and not statistically significant, so that the existence of SAKIP does not directly guarantee public information disclosure. These findings indicate that although SAKIP is designed as a comprehensive performance accountability system, its effectiveness is highly dependent on non-technical supporting factors such as human resource capacity, information technology infrastructure readiness, the commitment of regional leaders, a work culture that places accountability as a core value, and integration with public information disclosure mechanisms. In other words, high transparency tends to be influenced more by national regulations and the digitization of reporting that enforces standardization, rather than solely by the quality of SAKIP implementation. This is in line with information system theory, which emphasizes the importance of alignment between technology, processes, and people in producing information that is relevant, accurate, and accessible to the public. Therefore, optimizing SAKIP to support transparency requires a holistic approach that combines technical improvements with institutional capacity building and leadership commitment.